ICSBP-induced PD-L1 enhances osteosarcoma cell growth - Sung, Jee Young; Kim, June Hyuk; Kang, Hyun Guy; Park, Jong Woong; Park, Seog-Yun; Park, Byung-Kiu; Kim, Yong-Nyun (Frontiers in Oncology, 2022)
Background: Interferon (IFN) consensus sequence binding protein (ICSBP) is a transcription factor induced by IFN-γ. We previously reported that ICSBP expression promotes osteosarcoma progression by enhancing transforming growth factor-β signaling. In cancer cells, programmed death-ligand 1 (PD-L1) contributes to immune escape and may also be involved in tumor progression. Because IFN-γ induces expression of both ICSBP and PD-L1, we explored the association between ICSBP and PD-L1 expression in terms of osteosarcoma progression. Methods: Three osteosarcoma cell lines (Saos2, U2OS, and 143B) were employed. Gene expression was measured by qRT-PCR, and protein levels were assessed by immunoblotting. Effects of ICSBP levels on PD-L1 expression were evaluated in the ICSBP overexpressed cells and ICSBP-knockdown cells. Effects of PD-L1 expression on cell growth were examined by MTS assays, IncuCyte analysis, soft agar assays, and three-dimensional (3D) culture. Cell cycle and apoptosis were evaluated by FACS analysis of cells stained with propidium iodide (PI) and annexin V/PI, respectively. The anti-tumor effects of PD-L1 knockdown without or with doxorubicin treatment were evaluated in vivo in nude mice bearing ICSBP-overexpressing 143B cells xenograft. The clinical relevance of PD-L1 and ICSBP expression was evaluated immunohistochemically using a human osteosarcoma microarray and through analysis of publicly available data using Gene Expression Profiling Interactive Analysis2. Results: ICSBP overexpression upregulated PD-L1 expression in all three cell lines, whereas ICSBP knockdown decreased PD-L1 expression. PD-L1 knockdown attenuated cell growth and reduced colony-forming capacity in both soft agar assays and 3D culture. PD-L1 knockdown increased apoptosis and induced G2/M arrest, which was associated with decreased expression of survivin, cyclin-dependent kinase 4 (CDK4), cyclin E, and cyclin D1 expression, and increased expression of p27, phosphorylated Cdc2, and phosphorylated Wee1. PD-L1 knockdown decreased the growth of tumor xenografts and increased doxorubicin sensitivity of ICSBP-overexpressing 143B cells both in vitro and in vivo. PD-L1 was expressed in human osteosarcoma tissues and its expression was moderately correlated with that of ICSBP in osteosarcoma patients. Conclusion: ICSBP regulates PD-L1 expression in osteosarcoma cells and PD-L1 knockdown combined with doxorubicin treatment could represent a strategy for controlling osteosarcoma expressing ICSBP.